PERENCANAAN PERKUATAN TEBING JALAN AKIBAT LONGSORAN DI DESA TLEKUNG, KEC.JUNREJO KOTA BATU - KOROHAMA, FRANSISKUS X.T; Widodo, Esti; Sulistyani, Kiki Frida (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Retaining wall serves to hold the soil and prevent it from sliding danger. Either due to load rain, heavy soil itself or as a result of the load acting on it. At this time, construction of retaining wall is very often used in civil works construction although turns retaining wall had been long enough known in the world. Landslide that occurred along the river Konto Jln. Abd.Manan Wijaya Pujon caused by the dimensions of the retaining wall is too small so unstable to the safety factor (fs), the value of the safety factor in the review is a safety factor to bearing capacity, shear forces and stability against roll style. The purpose of this study was to analyze the causes of the collapse of the retaining wall and the planned re retaining wall that had collapsed. A retaining wall that is unstable to the shear force that is 1.28 1.5 (safe) and was stable against the bolsters: 3.9> 1.5 (safe). Keywords : soil retaining walls, Avalanches, Dimension, the stability of a retaining wall.